IMPACT OF MOOSE BROWSING ON FOREST REGENERATION IN NORTHEAST VERMONT - Andreozzi, Haley A.; Pekins, Peter J.; Langlais, Matt L. (Lakehead University, 2014)
Moose (Alces alces) play an important role in the ecological and economic resources of northern New England, a landscape dominated by commercial forests. This study measured the impact of moose browsing on forest regeneration in Wildlife Management Unit E1 in northeastern Vermont where moose density was considered high in the 1990–2000s. We surveyed 37 clearcuts categorized into 4 age classes (3–5, 6–10, 11–15, and 16–20 years old). The stocking rate (stems/plot) of commercial species ranged from 74–76% in the 3–5, 6–10, and 11–15 year age classes, increasing to 86% in the 16–20 year age class. The proportion of plots containing a commercial tree without severe damage was above the accepted threshold stocking level of 40–60% in all age classes. The proportion of plots containing a commercial hardwood stem declined with increasing age class; the opposite occurred with softwood stems indicating a possible shift from hardwood- to softwood-dominated stands from selective browsing pressure. Height of 11–20 year old stems was less than in New Hampshire, indicating that growth was possibly suppressed in Vermont due to higher moose density. Overall, browsing was not considered a major problem based upon stocking rates. Further study is warranted to evaluate whether compensatory growth occurs in response to reduced browsing as forests age and/or moose population density declines.